2021
DOI: 10.1021/acs.jnatprod.1c00293
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Manipulation to Trigger Production of Guaiane-Type Sesquiterpenes from a Marine-Derived Spiromastix sp. Fungus with Antineuroinflammatory Effects

Abstract: Epigenetic manipulation of a deep-sea sediment-derived Spiromastix sp. fungus using suberoylanilide hydroxamic acid (SAHA) induction resulted in the activation of a terpene-related biosynthetic gene cluster, and nine new guaiane-type sesquiterpenes, spiromaterpenes A-I (1–9), were isolated. Their structures were determined using various spectroscopic techniques, in association with the modified Mosher’s method, computed electronic circular dichroism (ECD) spectra, and chemical conversion for configurational as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…3-hydroxy-4-(4-hydroxyphenyl)-5-methoxycarbonyl-5-(4-hydroxy-3-formylben-zyl)-2,5-dihydro-2-furanone (9) was isolated from the gorgonian corals Echinogorgia aurantiaca endophytic fungus A. terreus. Two new butyrolactone derivatives, isobutyrolactone II (12) and 4-O-demethylisobutyrolactone II (18) were isolated from the soil-dwelling fungus A. terreus by Chen's team. An endophytic fungal strain Aspergillus versicolor derived from the rhizome of Paris polyphylla var.…”
Section: Aspergillus Terreusmentioning
confidence: 99%
See 2 more Smart Citations
“…3-hydroxy-4-(4-hydroxyphenyl)-5-methoxycarbonyl-5-(4-hydroxy-3-formylben-zyl)-2,5-dihydro-2-furanone (9) was isolated from the gorgonian corals Echinogorgia aurantiaca endophytic fungus A. terreus. Two new butyrolactone derivatives, isobutyrolactone II (12) and 4-O-demethylisobutyrolactone II (18) were isolated from the soil-dwelling fungus A. terreus by Chen's team. An endophytic fungal strain Aspergillus versicolor derived from the rhizome of Paris polyphylla var.…”
Section: Aspergillus Terreusmentioning
confidence: 99%
“…With a continuous increase in the number of new compounds, there have been several review articles on γ ‐AB [13–18] . For example, Joe and his co‐workers have reviewed the butenolactones in marine microbes, yet they focused only on three types of butenolides (rubrolides, cadiolides and prunolides), from marine tunicates [19] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, marine fungi have received widespread attention because of their tremendous capacity to produce structurally unique compounds with a broad range of pharmacological properties (Radic and Strukelj, 2012 ; Pang et al, 2016 ; Fang et al, 2021 ; Guo et al, 2021 ). Over the last 5 years, discoveries of new compounds from marine fungi have outpaced discoveries from all other marine phyla.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 50 years, about 20,000 natural products have been reported from marine microorganisms, but the number of natural products reported from deep-sea microorganisms is very low, less than 2%, and hadal trench (>6,000 m) microorganisms are hardly reported (Skropeta and Wei, 2014;Carroll et al, 2021). In recent years, with the rapid development of sample collection, identification, and culture techniques of microorganisms, the chemical study of deep-sea fungi has shown a dramatic increase, and researchers have found a wealth of novel active secondary metabolites with pro-angiogenic (Fan et al, 2015;Yan et al, 2022), antibacterial (Wang et al, 2016;Chi et al, 2020b), anti-inflammatory (Guo et al, 2021), anticancer (Chi et al, 2020a), and other biological activities (Wang et al, 2020) from deep-sea microorganisms.…”
Section: Introductionmentioning
confidence: 99%